Investigations of Phosphine Protected Silver Clusters and their Alloys in the Gas Phase and in Solution - (:unkn) unknown (Chennai, 2022)
Subnanometer sized clusters are made of a countable number of particles and they have dimensions in between the range of atoms and nanoparticles They exhibit molecule like properties and behave in a distinctly different manner compared to their bulk counterparts Due to their unique physicochemical properties they have attracted significant attention in the recent past Clusters can exist both in the gas phase and condensed phase The unprotected gas phase clusters are called naked clusters whereas condensed phase clusters are generally protected by the ligands As the major properties of such clusters predominantly depend on their size and structural arrangements the development of synthetic routes which allows precise tuning of the cluster cores with high chemical purity and monodispersity is an area of intense research A wide variety of synthetic approaches have been designed both in the gas phase and solution phase to synthesize clusters with divergent core sizes and elemental compositions Various characterization techniques have been used to gain a structural understanding of the clusters which is important to obtain a specific property of the nanoclusters for a particular application newlineThis thesis focuses on developing a synthetic strategy of gas phase and condensed phase silver clusters their essential characterization investigation of properties and applications Chapter 3 demonstrates a new method of forming gas phase naked silver clusters in air starting from a solution phase hydride and phosphine coprotected silver cluster Here we developed a strategic methodology in order to allow the desorption of ligands from Ag18H16TPP10 2 to facilitate the formation of Ag17 and Ag18H naked clusters outside xii the mass spectrometer These naked clusters are prepared by passing electrosprayed ligand protected clusters through a heated tube in the gas phase and their reactivity was compared by the reaction with oxygen Chapter 4 describes the gas phase reactivity study in between naked clusters Ag17 and acetylene outside
Keywords: Chemistry; Chemistry Applied; Physical Sciences